2020
DOI: 10.21203/rs.2.21581/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Geographic Access to Primary Care provider on Pediatric Behavioral Health Screening

Abstract: Objective : To assess the impact of geographic access to primary care providers (PCPs) on the receipt of behavioral disorder screening among children and adolescents from different racial/ethnic groups. Data Sources/Study Setting: The primary data source was 2013-2016 administrative claims data from a large pediatric Medicaid Managed Care Plan linked to the US Census data and the National Provider Identifier (NPI) Registry. Study Design: The study was a retrospective cohort design which was conducted using dat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Various studies have shown that increased distance to a health facility affects accessibility and tends to result in fewer primary care visits. [8][9][10] There is also evidence that the recent expansion of FQHCs nationwide has tended not to occur in areas with the highest rates of poverty. 11 In consideration of the issues associated with increased distance to care for children in poverty, the objective of this study was to determine if currently established FQHCs in Detroit are accessible to populations who require them, and to examine what areas in the city are most in need of the expansion of FQHCs.…”
Section: Karan Varshney Is Affiliated With the College Of Population ...mentioning
confidence: 99%
“…Various studies have shown that increased distance to a health facility affects accessibility and tends to result in fewer primary care visits. [8][9][10] There is also evidence that the recent expansion of FQHCs nationwide has tended not to occur in areas with the highest rates of poverty. 11 In consideration of the issues associated with increased distance to care for children in poverty, the objective of this study was to determine if currently established FQHCs in Detroit are accessible to populations who require them, and to examine what areas in the city are most in need of the expansion of FQHCs.…”
Section: Karan Varshney Is Affiliated With the College Of Population ...mentioning
confidence: 99%
“…It is important to remember that even a small increase in distance to pediatric care can have a large impact on access for patients with few resources and lack of transportation. [19][20][21] The trend is clear: pediatric inpatient care is more regionalized and concentrated. Intensive care beds are increasingly used, and the reason for that may be partly a financial response to decreased reimbursement rather than increased need for intensive care services.…”
mentioning
confidence: 99%